The evidence supporting methods of tooth width measurement: Part I. Vernier calipers to stereophotogrammetry - Naidu Devan; Freer Terrence J. (Sciendo, 2013)
Measuring tooth widths is a key component of orthodontic treatment planning. Over recent decades, many methods have been proposed to achieve this purpose. The current review highlights and describes the initial techniques. The evidence behind their use is presented along with a brief discussion of their benefits and shortfalls. With knowledge and understanding of the accuracy and limitations of the various measurement methods, the clinician may be better informed and therefore able to select the most appropriate method for clinical practice.